The Cult of Ivan the Terrible in Stalin's Russia - Perrie, M. author. aut Link
XV, 255 p.
Keywords: Ivan IV, the sixteenth-century Russian tsar notorious for his reign of terror, became an unlikely national hero in the Soviet Union during the 1940s. This book traces the development of Ivan's positive image, placing it in the context of Stalin's campaign for patriotism. In addition to historians' images of Ivan, the author examines literary and artistic representations, including Sergei Eisenstein's famous film, banned for its depiction of the tsar which was interpreted as an allegorical criticism of Stalin.